THE CAUSATIVE FACTORS IN EXCHANGE RATE BEHAVIOUR AND ITS IMPACT ON GROWTH OF NIGERIAN ECONOMY - Ogunsakin Sanya (European Scientific Journal, ESJ, 2013)
This paper examines the causative factors in exchange rate behavior and its impact on the growth of the Nigerian economy. The study employee’s con-integration and error correction as her estimation technique. The results obtained from the estimation were generally satisfactory. Specifically, they showed among others that all variables employed in the study are significant determinants growth of Nigerian Economy. The policy implications of our study are discussed. Among them are government should maintain more depreciated real exchange rate, higher saving to investment and lower expenditure relative to income.